2000
DOI: 10.1038/modpathol.3880073
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oncostatin M Expression in Keratoacanthoma and Squamous Cell Carcinoma

Abstract: Oncostatin M (OSM) is a 28-kDa glycoprotein, produced by stimulated macrophages and T lymphocytes, that inhibits the proliferation and induces differentiation of a number of different cell lines derived from solid tumors. To determine whether keratoacanthoma (KA) is unique or a variant of squamous cell carcinoma (SCC), we compared the immunohistochemical expression of OSM in the tumor cells and peri-and intratumoral macrophages of 21 mature KAs, 7 regressing KAs, and 27 SCCs. An inverse correlation was identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Comparable results were observed by Tran et al, they explained this indirectly proportional relationship by the possibility of presence of negative feedback mechanism between the tumor cells and the surrounding infiltrative macrophages (22). Inefficient OSM protein expression in neoplastic cells was also explained by Radtke et al who suggested the presence of abnormalities in various stages of OSMRβ production and activation (17) , furthermore, Lacreusetteet al, 2007 in their study on melanoma, identified epigenetic modifications in the OSMRβ promoter as histone deacetylation (14) .…”
Section: Discussion:-supporting
confidence: 70%
See 1 more Smart Citation
“…Comparable results were observed by Tran et al, they explained this indirectly proportional relationship by the possibility of presence of negative feedback mechanism between the tumor cells and the surrounding infiltrative macrophages (22). Inefficient OSM protein expression in neoplastic cells was also explained by Radtke et al who suggested the presence of abnormalities in various stages of OSMRβ production and activation (17) , furthermore, Lacreusetteet al, 2007 in their study on melanoma, identified epigenetic modifications in the OSMRβ promoter as histone deacetylation (14) .…”
Section: Discussion:-supporting
confidence: 70%
“…, in OSCC (22) , in prostate carcinoma (19) , in breast cancer (7), in esophageal SCC (12) and lastly in OSCC Chuerduangphui et al suggested that keratinocyte growth factor can stimulate OSM expression in tumor cells (2) .…”
Section: Discussion:-mentioning
confidence: 99%
“…Tran et al suggested that OSM overexpression in tumor cells was found in keratoacanthoma (a low-grade tumor) and in dermal squamous cell carcinoma, relative to normal tonsillar controls [18]. By contrast, Ryan et al could not demonstrate OSM expression in colon cancer cells, but strong expression in tumorinfiltrating neutrophils, indicating that these neutrophils were the main source of OSM secreted in this cancer [8].…”
Section: Discussionmentioning
confidence: 94%
“…Although the biologic behavior of keratoacanthoma is usually characterized by rapidly growing neoplasia, with regression in several months, there are cases of metastases (3). This has led to the controversy over whether keratoacanthoma are a distinct entity or a variant of cutaneous squamous cell carcinoma (16,17). In this study we have looked at two adhesion molecules in an attempt to explain the biologic behavior and pathogenesis of keratoacanthoma.…”
Section: Discussionmentioning
confidence: 99%